Allelopathy Index: a new mathematical assessment method for allelopathy studies - Kawa A. Ali (Zanco Journal of Pure and Applied Sciences, 2021)
A lab bioassay was conducted in Agricultural Engineering Sciences College labs to study the allelopathic influence of wild oat (Avena fatua L.) different plant parts shoot, root and seeds aqueous extracts with five concentrations (0, 25%, 50%, 75% and 100%) on three plant species Lettuce, Onion and Tomato seeds. Results indicated significant effect on all studied data, germination percentage, inhibition of germination, radicle length (cm); plumule length(cm); radicle dry weight, plumule dry weight; total seedlings dry weight (mg); radicle and plumule growth inhibition. The best bioassay plant was lettuce seeds for using as indicator in allelopathy studies. The main goal of the study was proposing five mathematical equations to indicate allelopathy index, the best two equations were chosen according to their best manipulation and demonstration based on total seedlings dry weight.